Infliximab for paradoxical reactions in pediatric central nervous system tuberculosis - Abo, Y-N; Curtis, N; Osowicki, J; Haeusler, G; Purcell, R; Kadambari, S; De Wachter, M; Vanden Driessche, K; Dekeyzer, S; Coleman, L; Crawford, N; Graham, S; et al. (Oxford University Press, 2021)
Paradoxical reactions in central nervous system tuberculosis (CNS-TB) are associated with significant morbidity and mortality. We describe 4 HIV-uninfected children treated for CNS-TB with severe paradoxical reactions unresponsive to corticosteroids. All made recovery after treatment with infliximab, highlighting the safety and effectiveness of infliximab for this complication, and need for prospective trials.